The Effect of Current Ratio and Return on Asset on Company Value in Property and Real Estate Companies Listed on the Indonesia Stock Exchange in the Period 2020-2022 - Yusra Muthia Rahman; Meri Diana Putri Purba; Ully Monica Br.Damanik; Cut Fitri Rostina (International Journal of Scientific Multidisciplinary Research, 2024)
The purpose of this study was to investigate the effects of Return On Assets (ROA) and Current Ratio (CR) on the Financial Value of Manufacturing Companies Listed on the Indonesia Stock Exchange in the Property and Real Estate Sub-Sector. 2020- 2022. The analysis considered both partial and simultaneous effects. Out of a population of 85 firms, 17 suitable sample companies were selected according to the specified criteria. This work is a quantitative study that specifically examines secondary data obtained using a ratio scale in statistical analysis. The employed analytical approach is multivariate linear regression analysis. The data analysis using the F test (simultaneous) shows that the value of the company is consistently and statistically significantly positively impacted by both the current ratio (CR) and return on assets (ROA). The Current Ratio (CR) has a somewhat negative and statistically significant impact on Company value, according to data analysis utilizing the partial t test. But the Return On Assets (ROA) has no bearing on the value of the company and is not statistically significant variable